Penyuluhan Hukum Tentang Layanan Bantuan Hukum Gratis di Posbakum Rutan Kelas 1 Surakarta - Kurnianingsih, Marisa; Hartanto, Hartanto; Firdaus, Lutfi`ah; Moestofa, Yoesoef (Civiliza Publishing, 2024)
The principle of